Smaug1 membrane-less organelles respond to AMPK and mTOR and affect mitochondrial function - Fernández Alvarez, Ana Julia (2022)
Smaug is a conserved translational regulator that binds numerous mRNAs, including nuclear transcripts that encode mitochondrial enzymes. Smaug orthologs form cytosolic membrane-less organelles (MLOs) in several organisms and cell types. We have performed single-molecule fluorescence in situ hybridization (FISH) assays that revealed that SDHB and UQCRC1 mRNAs associate with Smaug1 bodies in U2OS cells. Loss of function of Smaug1 and Smaug2 (also known as SAMD4A and SAMD4B, respectively) affected both mitochondrial respiration and morphology of the mitochondrial network. Phenotype rescue by Smaug1 transfection depends on the presence of its RNA-binding domain. Moreover, we identified specific Smaug1 domains involved in MLO formation, and found that impaired Smaug1 MLO condensation correlates with mitochondrial defects. Mitochondrial complex I inhibition upon exposure to rotenone, but not strong mitochondrial uncoupling upon exposure to CCCP, rapidly induced the dissolution of Smaug1 MLOs. Metformin and rapamycin elicited similar effects, which were blocked by pharmacological inhibition of AMP-activated protein kinase (AMPK). Finally, we found that Smaug1 MLO dissolution weakens the interaction with target mRNAs, thus enabling their release. We propose that mitochondrial respiration and the AMPK-mTOR balance controls the condensation and dissolution of Smaug1 MLOs, thus regulating nuclear mRNAs that encode key mitochondrial proteins.